Studies on the degradation of haemoglobin - Green, Margaret (Division of Medical Biochemistry, 2020)
The chemical relationship which exists between haemoglobin and bile pigments was first established in 1933, when, after monumental studies covering a period of 24 years, Hans Fischer and his colleagues succeeded in synthesizing bile pigments and protoporphyrin. He thereby demonstrated the fundamental tetrapyrrolic structure which is common to both haem and bilirubin. Prior to this, in vivo experiments on dogs performed by Mann, Sheard, Bollman and Blades showed that haemoglobin, injected into the arterial blood of the spleen or bone-marrow, produced a rise in the bilirubin content of the venous blood. Haematin was also evident in both arterial and venous blood.